Differences in Religious Attitudes Between People Who Participate and Do Not Participate in Religious Studies in Jorong Teluk Sikai Nagari Sungai Duo - Oktafiyatna, Nur 'Aine; Solfema, Solfema (Universitas Negeri Padang, 2023)
Recitation is an activity carried out by a number of individuals to gain religious knowledge and good morals or attitudes. The religious attitudes seen among the people in Jorong Teluk Sikai are still relatively low. This is thought to be because there are people who take part in the recitation and there are also people who do not take part in the recitation. This research aims to: (1) describe the religious attitudes of the people who attend the recitation, (2) describe the religious attitudes of the people who do not attend the recitation, and (3) determine whether or not there are differences in the religious attitudes of people who do and do not attend the recitation in Jorong Teluk Sikai. This research is research that uses quantitative methods with a comparative type. The instrument used was a questionnaire. The research subjects were 30 people who took part in the recitation and 30 people who did not take part in the recitation. The data analysis technique uses hypothesis testing with t test analysis (independent sample t-test). The results of this research are: (1) the religious attitudes of people who take part in the recitation are classified as good, (2) the religious attitudes of people who do not take part in the recitation are classified as poor, and (3) there is a significant difference between the religious attitudes of people who do and do not take part in the recitation at Jorong Sikai. It is hoped that the community will always support recitation activities as a form of non-formal education in society so that it will form good religious attitudes in society.